Inorganic carbon uptake strategies in coralline algae: Plasticity across evolutionary lineages under ocean acidification and warming. (October 2020) - Bergstrom, Ellie; Ordoñez, Alexandra; Ho, Maureen; Hurd, Catriona; Fry, Brian; Diaz-Pulido, Guillermo
Abstract: Dissolved inorganic carbon (DIC) assimilation is essential to the reef-building capacity of crustose coralline algae (CCA). Little is known, however, about the DIC uptake strategies and their potential plasticity under ongoing ocean acidification (OA) and warming. The persistence of CCA lineages throughout historical oscillations of p CO2 and temperature suggests that evolutionary history may play a role in selecting for adaptive traits. We evaluated the effects of p CO2 and temperature on the plasticity of DIC uptake strategies and associated energetic consequences in reef-building CCA from different evolutionary lineages. We simulated past, present, moderate (IPCC RCP 6.0) and high p CO2 (RCP 8.5) and present and high (RCP 8.5) temperature conditions and quantified stable carbon isotope fractionation ( 13 ε), organic carbon content, growth and photochemical efficiency. All investigated CCA species possess CO2 -concentrating mechanisms (CCMs) and assimilate CO2 via diffusion to varying degrees. Under OA and warming, CCA either increased or maintained CCM capacity, which was associated with overall neutral effects on metabolic performance. More basal taxa, Sporolithales and Hapalidiales, had greater capacity for diffusive CO2 use than Corallinales. We suggest that CCMs are an adaptation that supports a robust carbon physiology and are likely responsible for the endurance of CCA in historically changing oceans. Highlights: Ambient diffusive CO2 use of reef-building crustose coralline algae ranges from 35 to 65%. Algae largely maintain or increase bicarbonate use under ocean acidification and warming. Maintained or increased bicarbonate use is associated with sustained metabolic performance. Lineage predicts inorganic carbon uptake strategy. Proposed initial framework for inorganic carbon uptake strategies in crustose coralline algae.